Public and Private Partnerships and School Development among Higher Education Institutions in the Province of Capiz - Gaycebel Bernas de los Santos (IDEAS: Journal of Management & Technology, 2023)
This study was conducted to determine the extent of public and private partnerships and the degree of school development among Higher Education Institutions in the Province of Capiz. The researcher utilized a descriptive-correlational research design using quantitative and qualitative data. The data collection procedure was carried out with a sample population of 506 from the total population of 962 teaching and non-teaching staff among HEIs in the Province of Capiz for academic year 2022 – 2023. Proportionate random sampling was employed to determine the number of respondents per school. A researcher-made questionnaire was used to gather data. On the extent of public and private partnerships and the degree of school development among HEIs the seven stages of conducting an in-depth interview of Kvale (1996) were used to gather qualitative data. Statistical tools used were frequency count, percentage, mean, Mann-Whitney U test, Kruskall Wallis H test and Spearman rank correlation analysis. The findings of the study revealed that the PPPs in the province of Capiz as a whole and in terms of financing, professional expertise and logistics were perceived by the respondents to an occasional extent. Also, school development in the province of Capiz as a whole and in terms of instruction, research and extension resulted to an often response. The extent of PPPs varied on age, educational attainment, length of service and type of respondent. The degree of school development were the same regardless of age, sex, educational attainment and type of respondent. Significant relationship was found between the extent of public and private partnerships and the degree of school development among HEIs in the Province of Capiz.